Implikasi Penanaman Modal Asing (PMA), Penanaman Modal Dalam Negeri (PMDN) Terhadap Tenaga Kerja Dalam Meningkatkan Pertumbuhan Ekonomi Kota Surabaya - Azzalina Alsavira (Magister Manajemen STIE Bank BPD Jateng, 2021)
This research was conducted to determine the implications of foreign investment and domesticinvestment on labor and to see the contribution of labor absorption to Surabaya's economic growth.The method used is a qualitative descriptive research method which is supported by variousinformation media such as books, journals, articles, websites, and official documents related to theresearch topic. how big is the level of labor absorption on investment and the contribution of laborabsorption to Surabaya's economic growth and how are the efforts in managing investment in labor.The object of this research is in the Surabaya area in the 2011-2018 period. Based on the researchresults, the absorption of labor can have a positive impact on growth because it can reduceunemployment in Surabaya.